Mayores aglomeraciones urbanas españolas - José María Serrano Martínez (Cuadernos de Geografía de la Universitat de València)
The transformation of the cities in urban areas is a process that reaches recently in Spain he acquires strong intensity. That represents deep space changes. One of the important aspects refers to the transports and the accessibility. Here those are analyzed that use the highway through the roads of more capacity. Several cases are chosen highlighted by the specific problems, of different nature that everything originates.